Сulture role in consolidation potential development for urban communities in augmented social reality (Revista de Investigaciones Universidad del Quindío, 2022)
This present article mainly intends to evaluate conjunctive and disjunctive trends in modern urban culture development within the context of augmented social reality, which is characterized by hybridity, saturation with machinery and technology, the availability of communicators. The methodological foundation of the study is the materials of the sociological study carried out by the authors over the course of 2020 in three areas of Belgorod, including a) the questionnaire survey of the urban people (500 individuals) on the basis of a quota (by age and sex), multistage and zoned sampling; b) the expert surveys; c) Focus groups (urban youth, and mass media staff). Given the results of the conducted sociological study, the authors state the presence of a dynamic balance between disjunctive and conjunctive tendencies in the cultural sphere growth, at least in towns.
Keywords: social consolidation; urban community; urban culture; cultural waste; consolidation potential